Sappanone A Alleviates the Severity of Carbon Tetrachloride-Induced Liver Fibrosis in Mice - Jing Qi; Lanqian Li; Xueqing Yan; Wenxi Hua; Zixiong Zhou (Antioxidants, 2023)
Liver fibrosis is a major challenge to global health because of its various complications, including cirrhosis and hepatocarcinoma, while no effective treatment is available for it. Sappanone A (SA) is a homoisoflavonoid extracted from the heartwood of Caesalpinia sappan Linn. with anti-inflammatory and antioxidant properties. However, the effects of SA on hepatic fibrosis remain unknown. This study aimed to investigate the protective effects of SA on carbon tetrachloride (CCl4)-induced liver fibrosis in mice. To establish a liver fibrosis model, mice were treated intraperitoneally (i.p.) with CCl4 for 4 weeks. SA (25, 50, and 100 mg/kg body weight) was i.p. injected every other day during the same period. Our data indicated that SA decreased liver injury, fibrotic responses, and inflammation due to CCl4 exposure. Consistently, SA reduced oxidative stress and its-mediated hepatocyte death in fibrotic livers. Of note, SA could not directly affect the activation of hepatic stellate cells. Mechanistically, SA treatment lessened oxidative stress-triggered cell death in hepatocytes after CCl4 exposure. SA down-regulated the expression of M1 macrophage polarization markers (CD86 and iNOS) and up-regulated the expression of M2 macrophage polarization markers (CD163, IL-10, and Arg1) in livers and macrophages. Meanwhile, SA induced the activation of peroxisome proliferator-activated receptor gamma (PPARγ). However, decreased inflammatory responses and the trend of M2 macrophage polarization provided by SA were substantially abolished by SR202 (a PPARγ inhibitor) treatment in macrophages. Additionally, SA treatment promoted fibrosis regression. Taken together, our findings revealed that treatment with SA alleviated CCl4-induced fibrotic liver in mice through suppression of oxidative stress-mediated hepatocyte death and promotion of M2 macrophage polarization via PPARγ. Thus, SA might pave the way for a new hepatoprotective agent to treat liver fibrosis.